1993
DOI: 10.1210/edrv-14-1-59
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptors, Estradiol, and Diethylstilbestrol in Early Development: The Mouse as a Model for the Study of Estrogen Receptors and Estrogen Sensitivity in Embryonic Development of Male and Female Reproductive Tracts*

Abstract: To date, there is no conclusive evidence that ERs are present in preimplantation embryos. There are reports that estrogen is made by the rabbit blastocyst (61), and estrogens have been used to induce implantation in mice (62), but whether estrogens act through ERs in the embryo or in the maternal uterus is not known. ERs may be present in early embryos, but if so, levels are below the methods of detection used thus far. Perhaps with more sensitive immunodetection methods, it may be possible to detect ERs in em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 64 publications
7
45
0
1
Order By: Relevance
“…Cunha et al (5) used steroid autoradiography (ARG) to demonstrate that ER are undetectable in uterine epithelium (UtE) of neonatal BALB͞c mice, but are present in the mesenchyme͞stroma. Subsequent immunohistochemical studies confirmed that ER are undetectable in UtE from neonatal mice (1,6,7).…”
mentioning
confidence: 82%
“…Cunha et al (5) used steroid autoradiography (ARG) to demonstrate that ER are undetectable in uterine epithelium (UtE) of neonatal BALB͞c mice, but are present in the mesenchyme͞stroma. Subsequent immunohistochemical studies confirmed that ER are undetectable in UtE from neonatal mice (1,6,7).…”
mentioning
confidence: 82%
“…One of our working hypotheses is that under conditions in which the ER tends to exist as a monomer, the binding characteristics of two interacting molecules are different from that observed at high receptor concentrations. We contend that this low ER experimental condition better approximates ER concentrations found during early development [the ER content of uterine epithelial cells is low in fetal or newborn mouse (6) or rat (7), a period critical for estrogen-associated disorders (8)]. During these sensitive periods, chemical interactions resulting in synergy may occur at conditions in which critical ligand-receptor or receptorreceptor combinations occur.…”
Section: Kavita Ramamoorthy Fan Wang I-chen Chen Stephen Safe Departmmentioning
confidence: 92%
“…Nonetheless, the foetal rabbit ovary has been shown to produce oestradiol at the same age as the testis was able to synthesize testosterone [134]. Oestrogen receptors are present in the mouse embryo at the ambisexual stage [135], and they are also present in early embryos of other species [136,137]. Therefore, it is likely that oestrogens are involved in the differentiation of structures derived from the Mü llerian ducts, and they may affect differentiation of Wolffian derivatives.…”
Section: Sexual Differentiation and Developmentmentioning
confidence: 99%
“…During the critical period of sexual differentiation, one might anticipate that exposure of a chromosomal male to antiandrogenic xenobiotics would interfere with the androgen-dependent differentiation of the Wolffianderived structures and/or with the normal development of the male genitalia. Since oestrogen receptors are present in the male reproductive tract [54,55,57,135,[137][138][139][140], xenooestrogens could also interfere with the proper development of these structures. Likewise, xenoandrogens could masculinize the developing female foetuses, since the structures of their reproductive tracts contain androgen receptors [141].…”
Section: Sexual Differentiation and Developmentmentioning
confidence: 99%
See 1 more Smart Citation